Innovative Micro- and Nano-Architectures in Biomedical Engineering for Therapeutic and Diagnostic Applications - Nargish Parvin; Sang Woo Joo; Jae Hak Jung; Tapas K. Mandal (Micromachines)
The rapid evolution of micro- and nano-architectures is revolutionizing biomedical engineering, particularly in the fields of therapeutic and diagnostic micromechanics. This review explores the recent innovations in micro- and nanostructured materials and their transformative impact on healthcare applications, ranging from drug delivery and tissue engineering to biosensing and diagnostics. Key advances in fabrication techniques, such as lithography, 3D printing, and self-assembly, have enabled unprecedented control over material properties and functionalities at microscopic scales. These engineered architectures offer enhanced precision in targeting and controlled release in drug delivery, foster cellular interactions in tissue engineering, and improve sensitivity and specificity in diagnostic devices. We examine critical design parameters, including biocompatibility, mechanical resilience, and scalability, which influence their clinical efficacy and long-term stability. This review also highlights the translational potential and current limitations in bringing these materials from the laboratory research to practical applications. By providing a comprehensive overview of the current trends, challenges, and future perspectives, this article aims to inform and inspire further development in micro- and nano-architectures that hold promise for advancing personalized and precision medicine.